Evaluating the Five Kaizen Success Measurements through Employees Work Improvement and its Effects on Overall Work and Quality of Services: Empirical Study of Insurance Companies in Jordan - Omoush, Majd; Moflih, Monira; Almetrami, Reem (International Review of Management and Marketing, 2020)
The study aimed to understand the impact of the five Kaizen success measurements (Organizational Policy and Awareness, Education and training, Cultural factors, Internal processes assessment and recognition) on the overall quality of work and the quality through by Employees Work Improvement as mediated factor on Insurance Companies in Amman. The study used a questionnaire to gather data from distributed on the 300 employees used random sample was applied to the population of this study consisting of all executives, department managers and employees of the Insurance Companies in Amman, Jordan. The questionnaire consists of three sections. Least Square-Structure Equation Modeling (PLS-SEM) program was chosen and used in this study in an effort to examine and test the data associated with the hypotheses. The results show Kaizen methods positively effect on the employee work improvement of the companies of. The kaizen implement employee work improvement positively effect on overall work and quality of service, Kaizen implementation positively affects overall work and quality of service, Employee work improvement on overall work and quality of service is partially mediated between kaizen implementation and on overall work and quality of service of Insurance companies in Jordan. Additionally, small companies can use Kaizen to enhance the overall work with low cost compared to other methods of improvement, which can be of a high cost that small companies cannot afford. Keywords: Kaizen implementation, Education and training, Cultural factors, Employees work improvement, Overall work and quality of services, Insurance Companies JEL Classifications: G22, P36 DOI: https://doi.org/10.32479/irmm.9994